2020
DOI: 10.1002/cam4.3043
|View full text |Cite
|
Sign up to set email alerts
|

Piplartine attenuates the proliferation of hepatocellular carcinoma cells via regulating hsa_circ_100338 expression

Abstract: Hepatocellular carcinoma (HCC) is the commonest liver cancer 1 and is one of leading cause of cancer-related mortality. According to reports, more than 600 000 people die of HCC each year. 2 The majority of HCC occurs in sub-Saharan Africa and Asia, and it is more common in men rather than women. 3 Epidemiological and experimental studies have pointed out that the development of HCC may be caused and promoted by hepatitis B virus (HBV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Overexpression of circ-100338 promotes the proliferation of HCC through the miR-141-3p/ZEB1 axis. However, piplartine decreases expression of circ-100338, resulting in attenuated HCC proliferation ( 149 ). Si et al.…”
Section: Novel Implications Of Circrna In Hccmentioning
confidence: 99%
“…Overexpression of circ-100338 promotes the proliferation of HCC through the miR-141-3p/ZEB1 axis. However, piplartine decreases expression of circ-100338, resulting in attenuated HCC proliferation ( 149 ). Si et al.…”
Section: Novel Implications Of Circrna In Hccmentioning
confidence: 99%
“…Additionally, circRNAs have been proven and proposed to be related to several kinds of tumors. One research group revealed that high expression of circ-100338 could promote the proliferation of hepatocellular carcinoma cells [ 38 ]. In another study, Pang et al determined that circ_0072309 could retard the progression of NSCLC by inhibiting the expression of miR-580-3p [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…circSHKBP1 is highly expressed in the serum of patients with gastric cancer, which is also correlated with the prognosis of patients with gastric cancer (111). The abnormal expression of hsa_circ_0051443 (115), hsa_circ_100338 (116), circ-ZEB1.33 (117) in the serum of HCC patients is related to the prognosis of HCC patients. The abnormal expression of hsa_circ_0000370 in the blood of CRC patients is associated with the prognosis of CRC patients (118).…”
Section: Clinical Application the Diagnostic And Prognostic Roles Of Circrnas In Gi Tumorsmentioning
confidence: 98%